A COMPARATIVE CLINICAL STUDY OF BILVA MAJJA CHURNA AND KUSTUMBARI KALKA IN GARBHINI CHARDI W.S.R.TO EMESIS GRAVIDARUM (AYUSHDHARA, 2019)
Pregnancy is a dynamic state, during this period a lot of physiological and hormonal changes take place. These hormonal changes produce different kind of major to minor abnormalities in the pregnant women. Minor disorders are nausea, vomiting, constipation, gastric irritation, hemorrhoids, low back pain etc. Garbhini chardi (nausea and vomiting in pregnancy) is foremost common ailment encountered in clinical practice. If this nausea and vomiting are present in excess then it is called as emesis gravidarum. If not tackled effectively before or in time it may affect woman’s quality of life.The present study is taken up to evaluate clinically the effect of Bilva majja churna with Lajambu (Group-A), and Kustumbari kalka with Tandulodaka mixed with Sharkara (Group-B) and to compare the effect of both groups (15 in each group) of diagnosed patients of Garbhini chardi.Study revealed statistically extremely significant improvement was observed in both groups but on comparing the symptomatic improvement of both groups, it was found that average percentage of relief was higher in Group-A i.e. 71.66%, followed by Group-B i.e., 60.39%. It shows that Bilva majja churna with Lajambu is comparatively better to cure Garbhini chardi than Kustumbari kalka with Tandulodaka mixed with Sharkara.